Introduction - Pieruccini, Cinzia; Vescovi, Alessandro; Zullo, Federica (Governare la paura. Journal of interdisciplinary studies, 2014)
This Introduction by the editors of this special issue presents eleven contributions on the theme of fear in the Indian Subcontinent by Italian academic scholars